2-(2-Methoxybenzylidene) Hydrazine-1-Carbothioamide as Efficient Organic Inhibitor for Mild Steel in Hydrochloric Acid Solution - Ferkous, Hana; Djellali, Souad; Sahraoui, Rachid; Behloul, Hamza; Saoud, Khaoula; Cukurovali, Alaaddin (Springer International Publishing Ag, 2021)
The 2-(2-methoxybenzylidene) hydrazine-1-carbothioamide (MBHCA), a Schiff base, is tested as a corrosion inhibitor of mild steel in a hydrochloric acid medium (1 M). The addition effect of this compound on the metal behaviour is monitored using potentiodynamic polarization tests and gravimetric method. The results show the significant reduction in the corrosion rate of steel with the increase of the concentration of the Schiff base; the inhibition efficiency of MBHCA reaches a maximum value of 97.9% at 200 ppm. Polarization measurements reveal that the presence ofMBHCAdecreases the current and shifts the corrosion potential to higher values considerably indicating that this Schiff base acts as a mixed inhibitor with cathodic predominance.
2nd Euro-Mediterranean Conference for Environmental Integration-EMCEI -- OCT 10-13, 2019 -- Sousse, TUNISIA
Keywords: Schiff base; Corrosion inhibitor; Polarization; Adsorption